Level of ADL Dependence and Quality of Life of Post-Stroke Patients at Meuraxa Regional Hospital, Banda Aceh - Marianthi, Dewi; Afnita, Fitri; Ritawati; Nurhayati*; Nurhayati (Journal of Health, Medicine and Nursing, 2025)
Stroke is the third leading cause of death in the world after coronary heart disease and cancer in both developed and developing countries. One in 10 deaths is caused by stroke. In 2018, the highest number of provincial doctors diagnosed stroke patients was in East Kalimantan Province (14.7%) and the lowest in Papua Province (4.1%), while stroke patients in NAD province were as many as 7.8%. The objective was to determine the relationship between the level of dependence of Activity of Daily Living (ADL) and the quality of life in post-stroke patients at the Neurological Polyclinic and Al-Bayyan 1 Inpatient Room, Meuraxa Banda Aceh Hospital. This study uses a correlation method with a cross sectional approach. The research sample was 34 respondents taken by the Purposive Sampling technique. The research instrument used a modification of the Barthel index questionnaire and the EQ-5D questionnaire. The data was analyzed using the chi square statistical test. Based on the results of the study, it was found that stroke patients who had a partial dependence level of 47.1%, patients who experienced a poor quality of life of 58.8%. Based on statistical tests, it was obtained that the p value was 0.000 < 0.05 with a correlation coefficient of r = 0.695, which means that there is a strong relationship between the level of dependence of Activity Of Daily Living (ADL) and the quality of life in post-stroke patients at the Neurological Polyclinic and the Al-Bayyan Inpatient Room, Meuraxa General Hospital, Banda Aceh. The higher the level of dependence on a person's activities, the worse the quality of his life. It is recommended for patients to undergo medical rehabilitation for the prevention of physical disabilities, and family support in providing motivation to patients is important.